Implicit Game Aesthetics. (July 2015) - Bateman, Chris
Whatever games might be, people have strong opinions about what does or doesn't qualify as one. By dissecting the implicit value judgments motivating different definitions of "game, " the underlying aesthetic positions can be excavated, revealing a conceptual landscape of the aesthetics of play. Analysis of various definitions for game provided by both professional game designers and academics allows the identification of distinct aesthetic camps. These include (but are not restricted to) victory, problem, reward, imaginative, social, and uncertainty aesthetics. Additionally, a variety of refinements to these positions can be identified. Collectively, these aesthetic positions outline an answer to the question raised by Mary Midgley's observation that games and art can be unified because they deal with human needs that necessarily have a structure. This article provides a rough sketch of the shape of human play needs and asserts that the unity that can thus be attained must necessarily be diverse.